Psychometric evaluation of the Clinical Outcome in Routine Evaluation - General Population: Czech version - Klocek, Adam; Řiháček, Tomáš; Cígler, Hynek (Československá psychologie, 2021)
Objectives. This study aimed to assess psychometric properties, such as reliability, construct validity, and cut-off scores, for the Czech version of the Clinical Outcome in Routine Evaluation – General Population (GP-CORE) questionnaire, a tool usable for repeated measurement of psychological distress within routine clinical settings. Participants and setting. Two general populations and one clinical sample were used with N values of 420, 394, and 345, respectively. Hypotheses. One of the competing theoretical factor solutions will demonstrate the best fit. Statistical analysis. To examine the factor structure of the GP-CORE, a confirmatory multidimensional item response theory analysis (graded response model) was employed. Results. The best fitting model was a bifactor solution representing one content domain of overall distress and two item wording domains (positively and negatively worded items). Clinical cut-off scores were determined to be 1.85 (men) and 1.90 (women). Study limitations. The GP-CORE can be used as an unidimensional measure of overall distress, but users have to be aware of the influence of positive vs. negative item wording on the responses.
Keywords: Validation Studies as Topic; Česká republika; Statistics as Topic; průzkumy a dotazníky; lidé; validační studie jako téma; faktorová analýza statistická; Psychometrics; psychometrie; statistika jako téma; duševně nemocní; Surveys and Questionnaires; Persons with Psychiatric Disorders; Stress, Psychological; Factor Analysis, Statistical; Czech Republic; psychický stres; Humans